Fuzzy Logic Controller Design for Leader-Follower Robot Navigation - Tresna Dewi; Yudi Wijanarko; Pola Risma; Yurni Oktarina (IAES Indonesia Section, 2018)
Mobile robots are applied everywhere in the human's life, starting from industries to domestics. This phenomenon makes it one of the most studied subjects in electronics engineering. Navigation is always an issue for this kind of robot, to ensure it can finish its task safely. Giving it a “brain” is one of the ways to create an autonomous navigating robot. The Fuzzy logic controller is a good choice for the “brain” since it does not need accurate mathematical modeling of the system. Only by utilizing the inputs from sensors are enough to design an effective controller. This paper presents an FLC design for leader-follower robot. This FLC design is the improvement of FLC application in a single two differential-driven mobile robot. The relation between leader and follower robot is modeled linearly as a spring-damper system. Simulation proves the feasibility of the proposed method in several environment setting, and this paper also shows that the method can be easily extended to one leader and more than one follower's formation. The research in this paper has introduced in the classroom as the teaching-learning media to improve students' involvement and interest in robotics and robotics related class. This paper is also part of our campaign and encouragement for teachers and students to use low-cost and open source software since not all the universities in developing country can afford the expensive high-end software.